Ability of diastolic arterial pressure to better characterize the severity of septic shock when adjusted for heart rate and norepinephrine dose - Antoine Goury; Zoubir Djerada; Glenn Hernandez; Eduardo Kattan; Romain Griffon; Gustavo Ospina-Tascon; Jan Bakker; Jean-Louis Teboul; Olfa Hamzaoui (Annals of Intensive Care)
Abstract Background Septic shock is commonly associated with reduction in vasomotor tone, mainly due to vascular hyporesponsiveness to norepinephrine (NE). Although the diastolic arterial pressure (DAP)/heart rate (HR) ratio reflects vasomotor tone, it cannot be a reliable index of vascular responsiveness to NE (VNERi). We hypothesized that adjusting DAP/HR for the NE dose could yield a VNERi value (VNERi = DAP/(NE dose x HR)), knowledge of which can help guiding therapeutic strategies in cases of persistent hypotension despite NE (e.g., increasing NE doses vs. introducing additional vasopressors). For our hypothesis be valid, at least VNERi should demonstrate a stronger association with patient outcome than DAP, DAP/HR or mean arterial pressure (MAP)/NE dose, a global marker of NE responsiveness. Methods We conducted a post-hoc analysis of the ANDROMEDA-SHOCK database. Hemodynamic variables and initial NE doses were recorded at the randomization time-point, within 4 h of septic shock diagnosis. NE doses were expressed in µg/kg/min (using the bitartrate NE formulation). A multivariate model was employed to compare the associations between these variables and key clinical outcomes, including in-hospital mortality, numbers of vasopressor-free days and of renal replacement therapy (RRT)-free days up to day 28. Results The ANDROMEDA-SHOCK database included 424 patients with septic shock receiving NE. The median DAP was 52 mmHg [IQR: 45–50] and the median NE dose at inclusion was 0.2 µg/kg/min [IQR: 01-0.4]. In-hospital mortality was 43%. VNERi demonstrated the strongest association with in-hospital mortality compared to DAP, DAP/HR, and MAP/NE dose, emerging as the most significant covariate in the multivariate model. Similar findings were found for the associations with numbers of vasopressor-free days and RRT-free days up to day 28. The model revealed an inverted J-shaped relationship between in-hospital mortality and VNERi, with a nadir point at 6.7, below which mortality increased. Conclusions In patients receiving NE during early septic shock, VNERi demonstrated the strongest association with outcome compared to DAP, DAP/HR, and MAP/NE dose. Due to its physiological basis and robust association with outcomes, VNERi may serve as a valuable bedside marker of the vascular responsiveness to NE. This index could potentially be integrated into decision-making of early septic shock.